Assessing EU trade preferences for developing countries' development and food security - (:unkn) unknown (My University, 2015)
The EU has a long history of specific trade arrangements with developing countries. Under a variety of schemes, the EU allows developing countries to export goods to the Community market with reduced or zero duty. The stated objective is to encourage economic growth and to promote sustainable development in developing countries through their integration into the world trade system. Recently, these schemes have experienced significant reform. This applies particularly to the case of the Generalized System of Preferences and the arrangements affecting African, Caribbean, and Pacific countries. In addition, preferential (reciprocal) trade agreements are replacing non-reciprocal tariff concessions. We describe the current status of EU trade policy with developing countries, focusing on those where food security is a major issue. We assess the impact of selected preferential schemes, using an applied general equilibrium model. Our counterfactual simulations show that removing EU preferences will impact negatively on some developing country economies; both exports and gross domestic product will go down (particularly in North and Sub-Saharan African regions). Overall, our simulations suggest that EU preferential agreements provide export opportunities and contribute to higher incomes, particularly the least developed countries. However, their contribution to food security is indirect. Because of the magnitude of the prices and income changes which we measure at the aggregate level, the impact on food and nutrition security indicators seems limited. To explore in more depth the impact of EU preferences on the food security of particularly vulnerable segments of the population would require our simulations to be combined with household data.
Keywords: African Research